Comparison of Outcome of Primary Closure with Ileostomy in Enteric Perforation - Rafat Ullah, Bahri Room, Misbah Ullah, Muhammad Umar Khan Ghauri, Ghazala Bhatti, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Enteric perforation, often resulting from typhoid fever, is a life-threatening surgical emergency in many developing countries. Timely surgical intervention is critical, but the optimal surgical approach primary closure versus ileostomy remains debated. This study was conducted to compare the outcomes of these two operative techniques in terms of postoperative complications, recovery, and overall patient prognosis. To evaluate and compare the clinical outcomes of primary closure and ileostomy in patients presenting with enteric perforation. Methods: This prospective, comparative study was carried out at Ayub Medical College and its affiliated hospital from January 2021 to December 2021. A total of 103 patients diagnosed with enteric perforation were included. Based on intraoperative findings and clinical status, patients underwent either primary closure (n=51) or loop ileostomy (n=52). Demographic, intraoperative, and postoperative data were collected and analyzed using SPSS version 25. Postoperative outcomes including wound infection, fecal fistula, hospital stay, and mortality were compared. A p-value less than 0.05 was considered statistically significant. Results: Wound infection and wound dehiscence were more common in the ileostomy group, whereas fecal fistula was slightly more frequent in the primary closure group. Patients in the ileostomy group experienced longer operative time and hospital stay. Time to return of bowel function and initiation of oral intake was significantly shorter in the primary closure group. Mortality and reoperation rates were low and comparable between both groups. Conclusion: Both surgical techniques are effective in managing enteric perforation. However, in carefully selected patients with minimal contamination and single perforation, primary closure offers the advantage of faster recovery and fewer stoma-related complications. The choice of procedure should be individualized based on the patient's clinical condition and intraoperative findings. Keywords: Enteric perforation, typhoid, primary closure, ileostomy, postoperative complications, surgical outcomes, peritonitis.